Analysis of Dominican curricular approaches for early grade literacy of student population with specific needs of learning support - Pérez-García, Irene Altagracia (2022)
This research focuses on the inclusive education paradigm. To comply with the right of inclusive education, the Dominican Ministry of Education proposes a series of individualized curricular adjustments to support that student population with specific needs of learning support attending regular schools learn the necessary skills for their social development and are treated with equity. This study seeks to determine how aligned are the Dominican Curriculum Design and the individualized curricular adjustment guides with the evidence related to early grade literacy in student population with temporary educational needs. The design of this research The study is qualitative, cross-sectional, and descriptive. A literature review was carried out and selected the documents to be analyzed through a category tree. To complement the analysis of the texts, semi-structured interviews were conducted with people responsible for the creation and dissemination of the guides that were studied; data was processed with MAXQDA 2020, and then the information triangulated, the data collection occurred during the first four months of the year 2021. Results showed that many categories analyzed were absent in the documents and that the curricular adjustment guides do not address the acquisition of literacy in the specific needs of learning support population. The study concludes that the documents partially correspond to the evidence and that a proposal for curricular adjustments that responds to the specific needs of the child population is required.